2023
DOI: 10.1021/jacs.2c10206
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Ultrafast Stepwise Bidirectional Proton Relay in a Blue-Light Photoreceptor

Abstract: Proton relays through H-bond networks are essential in realizing the functionality of protein machines such as in photosynthesis and photoreceptors. It has been challenging to dissect the rates and energetics of individual proton-transfer steps during the proton relay. Here, we have designed a proton rocking blue light using a flavin (BLUF) domain with the flavin mononucleotide (FMN)–glutamic acid (E)–tryptophan (W) triad and have resolved the four individual proton-transfer steps kinetically using ultrafast s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
(103 reference statements)
1
9
0
Order By: Relevance
“…We tackle this problem by designing mutants to modulate the driving force of the proton relay, thereby capturing the PR intermediates and understanding their nature before we move to functional motifs. Hence, we designed Y6W/Q48E/W90F (referred to as FMN-Glu-Trp) in which Tyr6 is mutated into Trp to decouple the ET from the proton relay and Gln48 is substituted with Glu to reverse the sequence of the two PT steps . The PT from Glu to FMN happens before the PT from Trp to Glu due to the side chain of Glu (p K a = 4.15 in water) having a much lower p K a value than that of the native Gln (p K a (−NH 2 ) ∼ 15.1). , In this way, the purported PR intermediate has increased its accumulation from ∼3.3% relative to the FMN* population in the functional FMN-Gln-Tyr (from the kinetics simulation) to a significant 64% in the designed FMN-Glu-Trp, leading to the capture and quantification of the PR intermediate in FMN-Glu-Trp (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We tackle this problem by designing mutants to modulate the driving force of the proton relay, thereby capturing the PR intermediates and understanding their nature before we move to functional motifs. Hence, we designed Y6W/Q48E/W90F (referred to as FMN-Glu-Trp) in which Tyr6 is mutated into Trp to decouple the ET from the proton relay and Gln48 is substituted with Glu to reverse the sequence of the two PT steps . The PT from Glu to FMN happens before the PT from Trp to Glu due to the side chain of Glu (p K a = 4.15 in water) having a much lower p K a value than that of the native Gln (p K a (−NH 2 ) ∼ 15.1). , In this way, the purported PR intermediate has increased its accumulation from ∼3.3% relative to the FMN* population in the functional FMN-Gln-Tyr (from the kinetics simulation) to a significant 64% in the designed FMN-Glu-Trp, leading to the capture and quantification of the PR intermediate in FMN-Glu-Trp (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we designed Y6W/Q48E/W90F (referred to as FMN-Glu-Trp) in which Tyr6 is mutated into Trp to decouple the ET from the proton relay and Gln48 is substituted with Glu to reverse the sequence of the two PT steps . The PT from Glu to FMN happens before the PT from Trp to Glu due to the side chain of Glu (p K a = 4.15 in water) having a much lower p K a value than that of the native Gln (p K a (−NH 2 ) ∼ 15.1). , In this way, the purported PR intermediate has increased its accumulation from ∼3.3% relative to the FMN* population in the functional FMN-Gln-Tyr (from the kinetics simulation) to a significant 64% in the designed FMN-Glu-Trp, leading to the capture and quantification of the PR intermediate in FMN-Glu-Trp (Figure B). By elucidating all of the elementary steps, we found that after the photoinduced forward ET (1.0 ps, KIE = 1.0) forming the CS intermediate (FMN •– /Glu-COOH/TrpH •+ ), it will proceed with the forward PT2 (3.8 ps, KIE = 1.0) between the bridge and FMN •– forming the PR intermediate (FMNH • /Glu-COO – /TrpH •+ ) followed with forward PT1 (336 ps, KIE = 2.6) between Trp and the bridge forming the DR intermediate (FMNH • /Glu-COOH/Trp • ) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One type incorporates FMN as a chromophore: light-oxygen-voltage domain 2 (LOV2) [ 7 ], GIGANTEA [ 8 ], Vivid domain (VVD) [ 9 ] and its derivatives, including Magnets [ 10 ] and TULIPS [ 11 ] (VVD and its derivatives incorporate both FMN and FAD). The second type incorporates only FAD as a chromophore: cryptochrome 2 (CRY2) [ 12 ] and BLUF domain [ 13 ]. The third type incorporates p-coumaric acid as a chromophore: photoactivatable yellow protein (PYP) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%